Exploring the advantages of task-based learning to enhance reading skills. - Aguilar Cuenca, Aliza Arly (2024)
This research project, titled "Exploring the advantages of task-based learning to enhance reading skills," was “To explore Task-Based learning advantages to enhance reading skills on university students”. The study was conducted using a student centered constructivist approach, which promotes collaborative learning. It was a qualitative, phenomenological study that focused on a sample of students in their seventh semester at Universidad Peninsula de Santa Elena. The instrument used for data collection was a questionnaire of nine open-closed questions, which was administered through a focus group. The research demonstrated that task-based learning can effectively enhance reading skills therefore, it is important to carefully design and implement tasks in order to achieve the specific objective of enhancing reading skills.